Asymptotic Behavior of Solutions to the Damped Nonlinear Hyperbolic Equation - Yu-Zhu Wang (Journal of Applied Mathematics)
We consider the Cauchy problem for the damped nonlinear hyperbolic equation in n-dimensional space. Under small condition on the initial value, the global existence and asymptotic behavior of the solution in the corresponding Sobolev spaces are obtained by the contraction mapping principle.